Viable placental allograft as a biological dressing in the clinical management of full-thickness thermal occupational burns: Two case reports. Issue 49 (December 2017) - Johnson, Eric L.; Tassis, Elisabet K.; Michael, Georgina M.; Whittinghill, Susan G.
Abstract: Rationale: Occupational burn injuries can be detrimental and difficult to manage. The majority of complex cases are referred and managed at regional burn centers where access to specialized care is available. As an alternative to hospitalization with staged surgical procedures, placental products may be used for outpatient medical management of these common burn injuries, especially if access to a regional burn center is limited or restricted. Fresh amnion has been a treatment of choice in burns for more than 100 years. As a biological covering with a broad scope of potential uses, human placental membranes represent a dressing that is particularly advantageous for burn therapy. Recent advances in tissue-preservation technology have allowed for the commercialization of placental amnion products. Patient concerns: To address several complications associated with burn injuries—contractures, scar formation, and pain—a viable cryopreserved placental membrane (vCPM) (Grafix—PRIME, Osiris Therapeutics, Inc., MD) retaining the anti-inflammatory, anti-fibrotic, and antimicrobial properties of fresh placental tissues was chosen for clinical use in the 2 cases reported, where both patients had restricted access to the regional burn center. Diagnoses: Two cases of work-related extremity burns presented to a local rural hospital for immediate post-injury assessment. The 1 st case was of a man who sustained a 55.4 cm 2 full-thickness 3 rd degree thermal burn with exposed bone and tendon, to the left dorsal forefoot after having an industrial pressure washer caught on his work boot. The 2 nd case was of a female who sustained a 4.7 cm 2 full-thickness 3 rd degree crush burn to the dorsum extensor surface of her dominant hand's index finger after applying 80-pounds per square inch of heated pressure from a hydraulic press. Interventions: Both burn patients elected to continue their care at the outpatient-based wound and hyperbaric center, receiving a combination of weekly ad libitum debridement, applications of vCPM, and occupational therapy. Outcomes: Both burns reached timely wound closure, and patients regained full range of motion of the affected limb, allowing for early return to work. The average number of allograft applications was 7.5, allowing both patients to return to work in an average of 63.5 days without adverse events or post-treatment complications. Lessons: The incorporation of this product in the treatment of these complex burns prevented amputation in one patient, and skin autografting and potential index finger contracture-formation in the second patient. The incorporation of vCPM in burn management may offer a new approach to outpatient burn management and may mitigate several of the complications seen post burn injury, leading to favorable patient outcomes.